2016
DOI: 10.3201/eid2208.160270
|View full text |Cite
|
Sign up to set email alerts
|

Use of Unamplified RNA/cDNA–Hybrid Nanopore Sequencing for Rapid Detection and Characterization of RNA Viruses

Abstract: Nanopore sequencing, a novel genomics technology, has potential applications for routine biosurveillance, clinical diagnosis, and outbreak investigation of virus infections. Using rapid sequencing of unamplified RNA/cDNA hybrids, we identified Venezuelan equine encephalitis virus and Ebola virus in 3 hours from sample receipt to data acquisition, demonstrating a fieldable technique for RNA virus characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…134 MinION has already identified bacteria and viruses. [134][135][136] NEW MOLECULAR TECHNIQUES ARE NOT PERFECT Even with improvements in sensitivity, many infectious diseases do not release pathogen genetic material in the bloodstream in sufficient quantities to be diagnosed by NAAT using blood or serum samples. Blood culture theoretically can detect as little as one bacterium in a large volume culture bottle.…”
Section: Metagenomic Sequencing Can Identify Any Pathogenmentioning
confidence: 99%
“…134 MinION has already identified bacteria and viruses. [134][135][136] NEW MOLECULAR TECHNIQUES ARE NOT PERFECT Even with improvements in sensitivity, many infectious diseases do not release pathogen genetic material in the bloodstream in sufficient quantities to be diagnosed by NAAT using blood or serum samples. Blood culture theoretically can detect as little as one bacterium in a large volume culture bottle.…”
Section: Metagenomic Sequencing Can Identify Any Pathogenmentioning
confidence: 99%
“…The entire genome of a parapoxvirus isolated from a seal was obtained by combining data from Illumina next-generation sequencing with nanopore sequencing data 23 . One study has reported the detection of Venezuelan equine encephalitis virus from unamplified cDNA created from poly-A tailed RNA using cell culture grown viruses 24 . To the author's knowledge, the present study is the first using MinION as an aid in porcine health management.…”
mentioning
confidence: 99%
“…MinION has been extensively used in detecting known [177][178][179][180][181] and new [182] pathogen strains, for instance, of Ebola virus [183], Begomovirus [184] and Papillomavirus [185]. Curiously, MinION allows samples to be detected and genotyped within mere hours from sample collection, even "in the field", sometimes literally [186,187]. It has also been successfully used for rapid investigation of Dengue virus outbreak in Angola [188] and Ebola epidemic in Guinea [189].…”
Section: Long Read Sequencingmentioning
confidence: 99%